Environmental and genetic variation in body condition and blood profile of great tit Parus major nestlings - Claudia Norte, A; Sheldon, B; Sousa, J; Ramos, J (2009)
Health state parameters in natural populations can be used as bioindicators of environmental health if they respond to environmental cues. We studied to which extent health state parameters (morphological, biochemical, and haematological) were determined by the environment in which nestling birds were reared or by their genotype, using a cross-fostering experiment in great tits Parus major. Morphological parameters and plasma protein, had a higher environmental than genetic component of variance which could be related with food availability differing between rearing nests. Glutathione peroxidase, an enzyme involved in antioxidant protection, also had a relatively high environmental component of variance, suggesting that nestlings in different rearing nests were exposed to different degrees of oxidative stress. Plasma cholinesterases were more influenced by the birds' genotype than by the rearing environment. The parameters with the lowest residual variance and the highest environmental component of variance such as glutathione peroxidase, plasma protein and morphological parameters (tarsus length and weight) would be more adequate as bioindicators. © 2009 The Authors.